Differential gap location after radiofrequency versus cryoballoon pulmonary vein isolation: Insights from a randomized trial with protocol‐mandated repeat procedure. (22nd January 2023) - Sørensen, Samuel K.; Johannessen, Arne; Worck, René; Hansen, Morten L.; Ruwald, Martin H.; Hansen, Jim
Abstract: Introduction: Reconnections to pulmonary vein (PV) triggers of atrial fibrillation (AF) are the primary cause of AF recurrence after PV isolation (PVI) with radiofrequency (RF) or cryoballoon catheter ablation (CRYO), but method‐specific contributions to PV reconduction pattern and conductive gap location are incompletely understood. Methods: The objective of this radiofrequency versus cryoballoon catheter ablation for paroxysmal atrial fibrillation substudy was to determine procedure‐specific patterns of PV reconduction in a randomized population with protocol‐mandated repeat procedures, irrespective of AF recurrence. Each PV was assessed in turn and PV reconnection sites were identified by high‐density electroanatomical mapping and locating the earliest activation site. Gap locations were verified by PV re‐isolation. Results: In 98 patients, 81% versus 76% previously isolated PVs remained isolated after CRYO versus RF (risk ratio [RR]: 1.06; 95% confidence interval [CI]: 0.96–1.18; p = .28). There were no significant differences for any PV: left superior PV: 90% versus 80%; left inferior PV: 80% versus 78%; right superior PV: 81% versus 80%, and right inferior PV: 76% versus 73%. For each reconnected PV, 34% of ipsilateral PVs were also reconnected after CRYO compared with 64% after RF (RR: 0.54; 95% CI: 0.32–0.90; p = .01). After RF, gaps were clustered by the carina and adjacent segments, whereas they were more heterogeneously distributed after CRYO. Conclusion: Although RF and CRYO produce similar proportions of durably isolated PVs, gap locations appear to develop in procedure‐specific patterns. After RF, ipsilateral PV reconduction is more frequent and gap sites cluster by the carina, suggesting that this region should be selectively ablated for more durable PVI.